Avaliação do efeito do enalapril e do captopril sobre a produção de citocinas e de anticorpos - Castilho, Jacqueline Neres (2014)
Angiotensin-converting enzyme (ACE) inhibitors block the formation of angiotensin II (Ang II). They are also immunoregulatory drugs capable of inhibiting the production of proinflammatory cytokines such as tumor necrosis factor-alpha (TNF-α) as well as stimulate secretion of anti-inflammatory interleukins (IL), such as IL-10. However, the effects of these drugs on antibody production are not well understood in normal mice. Therefore, the objectives of this study are to evaluate the effects of enalapril and captopril on the humoral response and cytokine production in murine model. To verify the possible immunoregulatory action of ACE inhibitors, enalapril and captopril on the humoral response, we assessed the levels of IgM and IgG1 anti-OVA in sera of C57Bl/6 mice immunized with OVA in the presence of hydroxide gel aluminum with and without treatment with captopril or enalapril. IL-5 was assessed in sera collected at the end of the experiment. Analysis of anti-OVA antibodies and IL-5 was performed by enzyme-linked immunosorbent assays (ELISA), which were also included sera of control animals which were injected with phosphate buffered saline (PBS) and left untreated. Statistical analysis of the results of anti-OVA antibodies showed no significant difference in the levels of IgG1 and IgM specific for OVA comparing untreated animals with those treated with enalapril or captopril. IL-5 was detected in two of the five immunized animals and untreated. Two out of five mice in the control group also presented IL-5. From the results it can be concluded that captopril and enalapril do not significantly regulate the production of IgG1 and anti-OVA IgM. As all immunized animals that were treated with enalapril or captopril showed serum IL-5 levels below the detection limit (4 pμ/mL) of the reaction used to evaluate it, we can not state that these drugs inhibit the production of systemic IL-5 in this model.